Herpetofauna de la cuenca baja del Río Temascatio, Irapuato, Guanajuato, México - Cadena-Rico, Samuel; Leyte-Manrique, Adrian; Hernández-Salinas, Uriel (Instituto de Ecología, A.C., 2020)
Mexico is considered one of the countries with one of the most notable diversities of amphibians and reptiles in the world, with around 1,290 species and a high degree of endemism. This makes Mexican herpetofauna worthy of analyse under taxonomic, ecological and biogeographic hypotheses. In a context of species diversity, the present work focuses on measuring the composition and diversity of amphibians and reptiles distributed in three types of vegetation (tropical deciduous forest = TDF, xerophytic scrub = XS and oak forest = OF) present in the Río Temascatio lower basin, municipality of Irapuato, Guanajuato, Mexico. The herpetofauna in the study area is composed of 14 families, 23 genera, and 31 species. According to the Shannon-Wiener index, the OF presented the highest value of species diversity (6.25), followed by the TDF (5.29) and the XS (4.16). The abundance range curves indicated that, both in the rainy and dry seasons, the herpetofauna of the basin is composed mostly of rare species and few abundant species. According to the Mexican regulation NOM-059, three species of anurans and nine species of reptiles are under some category of risk. Only one species of anuran is listed as vulnerable according to the IUCN Red List. The EVS, an index that evaluates the environmental vulnerability status of Mexican amphibians and reptiles, considers four species of anurans at high risk, two at medium risk, and five at low risk. For reptiles, this index places six species at high risk, six at medium risk, and eight at low risk. This work represents the first list of the amphibian and reptile fauna of the Río Temascatio lower basin, which can be considered as an information base for developing future studies involving ecological and biogeographical aspects, aimed at proposing conservation strategies for a little-explored fauna in the northeastern portion of the Mexican Bajío.